Triangle of Political Behavior in Governmental Organizations: An Analysis of the Black, White, and Gray Spectrum of Political Behavior Using Meta-Synthesis Approach - Tir , Mohammad; Kia Kojouri, Davood; Gilanipour , Javad; Rahmaty , Maryam (Digital Transformation and Administration Innovation, 2026)
Political behavior in governmental organizations refers to a set of informal actions and interactions that employees and managers engage in beyond their formal job descriptions to gain, maintain, and increase influence, power, and access to scarce resources. The primary objective of the present study is to provide a model of political behavior in governmental organizations using the meta-synthesis method. This study employed a qualitative and development-oriented research design. The seven-step method of Sandelowski and Barroso (2007) was used to examine the model of political behavior in governmental organizations through meta-synthesis. The statistical population included scientific articles, academic theses, and books. A total of 157 sources were reviewed, and ultimately 60 sources were selected and analyzed. Through a purposive meta-synthesis approach, the components related to political behavior were identified. The reliability of the components was confirmed using the Kappa coefficient. SPSS version 19 was used for statistical analysis. The findings of the study revealed that political behavior in governmental organizations includes three categories: black political behavior (33 components), white political behavior (37 components), and gray political behavior (20 components). Understanding political behavior enables managers to predict and manage such actions instead of directly confronting and eliminating them, which is often impractical.